Partial Pericardial Agenesis - Akila Bersali; Faisal Nabi (Methodist DeBakey Cardiovascular Journal)
Congenital absence of the pericardium is a rare anomaly, affecting the left pericardium (86%) more than the right, with male predilection distribution (3:1). In the majority of cases, the condition is asymptomatic. We describe a case of a 55-year-old female with a history of chronic hypercapnic respiratory failure secondary to restrictive lung disease who was referred to cardiovascular magnetic resonance (CMR) lab for shunt evaluation based on right ventricular pressure overload and paradoxical septal motion.